Asphalt Mixtures with Modified Binders in the Republic of Panama - Botasso, Gerardo (2025)
Chapter 24th, of road construction specifications of the Ministry of Public Works in Panama (MOP), deals with asphalt mix construction and design requirements, including mixes using modified asphalts. This article presents the technical specifications review for modified asphalt mixes, under a cooperation agreement between Panama and Argentina, given that Panama is starting to use this mix type in recent projects.The specs review was performed in 2008 to define the metodology to evaluate the asphalt binder, the agregate- asphalt adhesion requirements and the expected performance of modified asphalt mixes, using the properties of typical imported asphalt in Panama and the local agregates. The agregates in Panama usually have high porosity values and high abrasion losses after tested. This article also shows the updating process for quality control laboratories facilities in MOP Panama, to deal with the new requirements for controlling modified asphalt mixes, since this laboratory has the mission of executing technical supervision of public works. It is also shown that these actions must be supported by a comprehensive training program for all people involved in road construction quality control and supervision.